The Effectiveness of Logotherapy Based on Rumi’s Thoughts on Happiness, Psychological Well-being, and Life Enthusiasm in Mothers of Children with Cancer - Hajitabar, Nahid; Norouzi, Asghar; Hassanzadeh, Ramazan (Psychology of Woman Journal, 2024)
Objective: The present study aimed to examine the effectiveness of logotherapy based on Rumi’s thoughts on happiness, psychological well-being, and life enthusiasm in mothers of children with cancer at Amir Kola Children’s Hospital in Babol. Methods and Materials: This quasi-experimental study employed a pretest-posttest design with a control group. The research population included all mothers of children with cancer who had visited Amir Kola Children’s Hospital in Babol during 2023-2024. The sampling method was non-random and purposive, with a sample size of 30 mothers. Data were collected using the Oxford Happiness Questionnaire (2001), Ryff’s Psychological Well-being Scales (1989), and the Life Enthusiasm Questionnaire by Hasanzadeh (2015). Subsequently, logotherapy based on Rumi’s thoughts (Norouzi, 2017) was implemented over eight sessions, each lasting 1.5 hours, for the experimental group. A posttest was then conducted on both the experimental and control groups. Findings: The results of data analysis indicated that group logotherapy had a significant positive effect on the happiness, psychological well-being, and life enthusiasm of mothers of children with cancer. Based on the reported p-value (P < 0.05), a significant difference was observed between the mean scores of happiness, psychological well-being, and life enthusiasm between the two groups. In the comparison of posttest to pretest scores, the experimental group showed a significant increase in all three components—happiness, psychological well-being, and life enthusiasm—compared to the control group. Conclusion: Therefore, it can be concluded that logotherapy based on Rumi’s thoughts is effective in enhancing the happiness, psychological well-being, and life enthusiasm of mothers of children with cancer.